Undernutrition risk and nutritional screening implementation in hospitals: Barriers and time trends (2019-2020) - Taipa Mendes, AM (2021)
Background & aims: Undernutrition screening is the starting point for high-quality nutrition care. In Portugal, the systematic nutritional risk assessment became mandatory for every inpatient in hospitals of the National Health System in 2019. The aims of this study were to describe the country's nutritional risk prevalence of hospitalized patients, and the experience of implementing a systematic undernutrition screening method, including time trends, barriers, and facilitators. Methods: This research was carried out in Portuguese Public Hospitals (n = 49) and included both the analysis of data from health information systems between January 2019 and December 2020 and from an online survey. The performance indicators are described for 38 hospitals that use the SClinico electronic health records software provided by the Ministry of Health. The Nutritional Risk Screening 2002 (NRS 2002) was applied to adult patients and the STRONGkids to paediatric patients. In order to assess barriers and facilitators the online survey was applied to all public hospitals (n = 49), including Hospital Centres and Local Health Units. Results: In 2020, 25.5% of the screened patients were nutritionally at risk. There was a significant increase in the proportion of patients screened from the pre- (10.6 ± 1.9%) to the post-adaptation period of the electronic health record (23.3 ± 4.8%, JulyDecember 2019, and 25.4 ± 2.2%, JanuaryJune 2020) (p < 0.001). Data from 41 Hospital Centres and Local Health Units (84%) were obtained from the online survey. The major barriers identified were the lack of human resources (89.7%) and equipment (41.0%), as well as insufficient knowledge about the role of undernutrition screening (35.9%). The most-reported facilitators were the integration of undernutrition screening to electronic health records (22.2%) and good multidisciplinary articulation (36.1%). Conclusion: The high prevalence of nutritional risk justifies the mandatory nutritional screening, which leads to the improvement of the quality of hospital care. However, local and national efforts are warranted to adapt nutritional screening policies to local conditions and to increase and improve its implementation. (c) 2021 European Society for Clinical Nutrition and Metabolism